An Arabidopsis thaliana methyltransferase capable of methylating farnesoic acid - Yang, Yue (2005)
We previously reported the identification of a new family of plant methyltransferases (MTs), named the SABATH family, that use S-adenosyl-l-methionine (SAM) to methylate a carboxyl moiety or a nitrogen-containing functional group on a diverse array of plant compounds. The Arabidopsis genome alone contains 24 distinct SABATH genes. To identify the catalytic specificities of members of this protein family in Arabidopsis, we screened recombinantly expressed and purified enzymes with a large number of potential substrates. Here,we report that the Arabidopsis thaliana gene At3g44860 encodes a protein with high catalytic specificity towards farnesoic acid (FA). Under steady-state conditions, this farnesoic acid carboxyl methyltransferase (FAMT) exhibits K(M) values of 41 and 71 μM for FA and SAM, respectively. A three-dimensional model of FAMT constructed based upon similarity to the experimentally determined structure of Clarkia breweri salicylic acid methyltransferase (SAMT) suggests a reasonable model for FA recognition in the FAMT active site. In planta, the mRNA levels of At3g44860 increase in response to the exogenous addition of several compounds previously shown to induce plant defense responses at the transcriptional level. Although methyl farnesoate (MeFA) has not yet been detected in Arabidopsis, the presence of a FA-specific carboxyl methyltransferase in Arabidopsis capable of producing MeFA, an insect juvenile hormone made by some plants as a presumed defense against insect herbivory, suggests that MeFA or chemically similar compounds are likely to serve as new specialized metabolites in Arabidopsis.